APLIKASI “PENGENALAN BUAH DAN BINATANG” BERBASIS AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN PADA PENDIDIKAN ANAK USIA DINI - Noer Azizah Rosita Dewi Suwoto (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2021)
Sustainable Development Goals (SDGs) is a continuation of the Melenial Development Goals (MDGs) as joint development ambitions in the period of 2015 to 2030. Sustainable Development Goals (SDGs) have 17 development goals with 169 targets, one of which is to ensure the quality of education inclusive and equitable for all levels. Quality education in this case is intended to ensure that all children, both girls and boys, can complete quality basic education and lead to relevant and effective education.Improving the quality of education carried out by the government aims to prepare alpha generations so that they can compete with other countries in the future. The preparation starts from early childhood education which is taken by children aged 0-6 years who tend to think in a concrete way. The need for learning media to explain something abstract and can be understood by early childhood. Therefore interesting media is highly recommended as an alternative in learning. However, in the era of the industrial revolution 4.0 has not been optimally entered into all fields including education. In this decade there emerged technological development innovations that could be used in education, especially for the Early Childhood Education. Augmented Reality is a technology that has been developed by Programmers to improve the quality of Indonesian education. Seeing the problems and opportunities that are being experienced by the development of education in Indonesia, through the technology of Augmented Reality developed an application called the Pengenalan Buah dan Binatang that can be used as a medium of learning that involves and trains the senses in early childhood. According to research conducted by the British Audio Visual Association shows that 75% of people obtain information from visual, 13% from hearing audio, 6% from touch and touch, and 6% from kiss/tongue. It also needs support and cooperation between children, parents and the community to foster cooperation in the face of the Industrial Revolution 4.0 era.